Writers' War Board records - Writers' War Board
Chiefly correspondence with writers and government agencies concerning dissemination of information and propaganda during World War II. Also includes minutes of meetings, writings, subject files, scrapbooks, photographs, posters, and other records. Individuals represented include Clifton Fadiman, Alan Green, Christopher LaFarge, Margaret Leech, and Rex Stout.
Non-governmental organization with headquarters in New York, N.Y.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Fadiman, Clifton, -- 1904-1999.; Green, Alan, -- 1906-1975.; LaFarge, Christopher, -- 1897-1956.; Leech, Margaret, -- 1893-1974.; Stout, Rex, -- 1886-1975.; Authors, American; World War, 1939-1945 -- Propaganda; New York (N.Y.) -- Intellectual life -- 20th century